A co-feeding strategy of formate and H2 for methanogens – Enhancing growth parameters and methane production - Björn Sabel-Becker; Nicolas Patrick Jost; Anne-Kristin Kaster; Dirk Holtmann (Journal of CO2 Utilization)
Carbon dioxide emissions could be reduced by developing alternative production processes based on a renewable C1 building block. Formate could link the electrical and chemical sectors as its production can be realized through the electrochemical reduction of CO2. Its function could be either a long-term energy storage medium or a starting material in a bioprocess. In this study, formate served as an energy and carbon source for methane production with a formatotrophic mixed culture. It was successfully shown that the theoretical maximum of 0.25 methane per formate can be overcome by co-feeding formate with H2. The production yield doubled to 0.555 ± 0.021 in a CO2-free buffer and 0.591 ± 0.032 in a bicarbonate buffer. With excess CO2 in the bicarbonate buffered culture, it was shown that the H2 transfer rate was the limiting factor for this process. Otherwise, the bicarbonate buffered culture outperformed other buffered cultures in terms of start-up time, formate consumption, and methane production rate. The additional CO2 in the gas phase might have enhanced the growth of methanogens in an early stage of cultivation. 16S sequencing revealed the composition of the cultures. With nearly 25 %, the genus Methanofollis was one of the most dominant strains and the only detectable methanogen in the mixed culture, making it an interesting candidate for formatotrophic methane production. In summary, the co-feeding strategy might be an approach to utilizing formate as feedstock for the bioproduction of methane if hurdles like the H2 transfer rates can be overcome.